“Just How Are We Going to Satisfy Our Research Customers” - Follett, Sir Brian K. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
The challenge is how to provide our researchers with ready and unimpeded access to all types of research information, whether it is held on paper or electronically. This has been, of course, the role of research libraries for hundreds of years so why is it a particular challenge at the present time? May I suggest that the problems are acute because a number of factors are all occurring at the same time. In this paper I will mention some of these.